The dominant of values and lifestyles (VALS) between generations in Malaysia / Ahmad Subhi Zolkafly - Zolkafly, Ahmad Subhi (Universiti Teknologi MARA, Kedah, 2022)
Malaysian citizen consist of four different cohort that are baby boomers, generation-X, generation-Y and millennial. Each generation produces a different value and lifestyles (VALS) dominancy based on their living styles, occupation, and social status. This paper highlighted on the dominancy of the Values and Lifestyles (VALS) between each generation in Malaysia. The respondents of the questionnaires were selected by using snowball approach and analyzed using Orange Application. This application produces a graph which is then translated into a readible table.